P733 Comparative Analysis of Monotherapy and Combination Biological Therapy for Crohn's disease and ulcerative colitis: Results from a Multi-Country Study in Europe. (25th January 2019) - Robinson, P; Bergman, R; Collins, P; Karki, C; Lu, Y
Abstract: Background: To assess patterns of biological monotherapy and combination therapy usage in Crohn's disease (CD) and ulcerative colitis (UC) patients across the EU5 (UK, Germany, France, Spain, Italy) over the period of 4Q2017 (4Q17) to 3Q2018 (3Q18), and the effects on remission rates. Methods: Data from Ipsos Autoimmune Therapy Monitor, a multi-centre medical chart-review study of CD and UC patients was conducted among physicians (mostly gastroenterologists) from EU5 to collect de-identified data on patients currently on a biologic/biosimilar or discontinued from one within past 3 months. Physicians were recruited from a large panel to be geographically representative in each country. Patient charts of 4–6 successive patients visiting each centre/practice during study periods 4Q17 and 3Q18 were selected and stratified based on biologic use (monotherapy or combination therapy). Demographics, clinical characteristics, treatment patterns and disease status (incl. assessment of 'disease remission', per physician clinical judgement) was collected and analysed using descriptive statistics. Results: In 4Q17, 194 physicians abstracted data on 1037 CD and 713 UC patients; in 3Q18, 207 physicians abstracted 1148 CD and 745 UC patients. CD combination therapy rates remained stable over time (4Q17: 30.8%, 3Q18: 30.6%). In UC patients, the proportion receiving combination therapy decreased slightly over time (4Q17: 49.9%, 3Q18: 46.8%) The proportion of immunologic naïve CD combination therapy patients increased over time (4Q17: 15.0%, 3Q18: 27.1%, p ≤ 0.01), similar increase was also seen in UC patients (4Q17: 31.2%; 3Q18: 43.8% ( p ≤ 0.01)). The rate of combination therapy with steroid use remained stable among CD patients (4Q17: 36.1%; 3Q18: 40.7%), however, increased among the UC patients (4Q17: 23.0%; 3Q18: 33.8%, p ≤ 0.05). Significant increase in remission rates were seen among the CD patients on monotherapy (4Q17: 75.3%, 3Q18: 80.1%, p ≤ 0.05), however, rates remained stable for combination therapy patients (4Q17: 58.0%, 3Q18: 58.8%). Remission rates among monotherapy UC patients remained stable (4Q17: 71.1%, 3Q18: 76.5%) but there was a significant decrease in remission rate among combination therapy patients (4Q17: 73.0%, 3Q18: 64.5%, p ≤ 0.05). Conclusions: In this study, there was a significant increase in combination therapy use among biologic naïve CD and UC patients from 4Q17 to 3Q18 suggesting that physicians are taking a more progressive approach to treating patients. However, CD patients on monotherapy showed better remission rates compared with others patient groups. Further study on treatment patterns and potential confounders impacting the remission rates is warranted.